The Influence Of Ceo Power On Environmental, Social, Governance (Esg) Disclosure In Infrastructure Companies Listed On The Asian Stock Exchange In The 2019-2023 Period - Irhamsi Gotea (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study focuses on analyzing the influence of CEO power on ESG disclosure in infrastructure companies listed on the Asian Stock Exchange from 2019 to 2023. Globally, the implementation of ESG principles is increasingly considered crucial as a manifestation of a company's commitment to sustainability, in line with the sustainable development goals supported by the G20 countries. CEO PowerCEO duality, including share ownership and dual roles as CEO and chairman of the board of directors, are important factors that can influence a company's strategic decisions. However, this study found that CEO duality significantly influences ESG disclosure in companies. Meanwhile, CEO ownership does not significantly influence ESG disclosure. This suggests that CEO leadership structure does not directly drive increased transparency in ESG disclosure. This study suggests that companies should not rely solely on CEO leadership structure to improve ESG disclosure, but should also consider other factors such as board composition and external regulations. This is expected to provide a deeper understanding of the factors influencing ESG disclosure and how this can support better and more sustainable corporate governance practices.